Values of Bongkel in Gerduren Village Banyumas Regency - Wijaya, Barkah Bangkit; Sunarto, Sunarto; Utomo, Udi (Universitas Negeri Semarang, 2018)
Bongkel art was created by Kerta Wijaya as an expression of self-motivated by dissatisfaction of farmworker regarding the results of work. Development of Bongkel art by Gerduren Village community functioned as a medium of entertainment, communication between Gerduren community while keeping the fields. Based on the reason, the researcher examines the values contained in Bongkel art. This research is qualitative research. The location in this research is in Gerduren village of Banyumas Regency. Data collection techniques consist of observation, interview, and document study. Data validity technique used in this research is triangulation. Miles and Huberman analysis model is used as data analysis technique. Bongkel result is analysed using the value of axiology. The analysis is using some values on art Bongkely that divine the value reflected in the activity. For exmples: Religion value in sedekah bumi, the good living value reflected in the activities of visiting family members, the truth value seen in traditional clothing used by society. This clothes uphold the values and norms agreed by Banyumas community, while the value of beauty is seen from the relationship between human beings, man with God and man with nature.